2014
DOI: 10.5657/kfas.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Rhus javanica against the Fish Pathogens Vibrio ichthyoenteri and Streptococcus iniae

Abstract: The antibacterial activities of methanol extracts of 19 commercial herbal medicines were measured against the fish pathogens Vibrio ichthyoenteri and Streptococcus iniae, which cause several fish diseases. Rhus javanica showed the strongest antibacterial activity against V. ichthyoenteri and S. iniae. The methanol extract of R. javanica was extracted further using several organic solvents with different polarities. The extract from the ethyl acetate fraction showed strong activity against both fish pathogens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As a result, industrial development has been accompanied by some practices potentially damaging to human and animal health that include passing large amounts of veterinary drugs into the environment [ 2 3 ]. Accordingly, various studies have been made to search for antimicrobial agents from natural materials like Rhus javanica extracts and bee venom for application to aquaculture [ 4 5 ]. Such natural substances are safer for the human body than antibiotics and chemicals and are not as concerned with resistant bacteria [ 6 ].…”
mentioning
confidence: 99%
“…As a result, industrial development has been accompanied by some practices potentially damaging to human and animal health that include passing large amounts of veterinary drugs into the environment [ 2 3 ]. Accordingly, various studies have been made to search for antimicrobial agents from natural materials like Rhus javanica extracts and bee venom for application to aquaculture [ 4 5 ]. Such natural substances are safer for the human body than antibiotics and chemicals and are not as concerned with resistant bacteria [ 6 ].…”
mentioning
confidence: 99%
“…Owing to the presence of various bioactive constituents and their stability, many researchers have explored biologically active natural products, including those that have anti-inflammatory properties [ 23 , 24 , 25 ]. In particular, phenylpropanoid compounds isolated from natural products are known to exhibit anti-inflammatory activities [ 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhus javanica has been used to treat dysentery and diarrhea in different Asian countries including Korea, China, and Japan [15]. Several studies showed that, Rhus javanica extract was effective against animal husbandry disease-related bacteria like Listeria monocytogenes and Staphylococcus epidermidis, fish pathogens like Vibrio ichthyoenteri and Streptococcus iniae [16,17]. Leaves of Rhus javanica primarily contains gallic methy lester, syringic acid, protocatechuic acid, and 1, 2, 3, 4, 6-penta-O-galloyl--Dglucose [18].…”
Section: Discussionmentioning
confidence: 99%